Importance of satisfaction level with initiatives toward the national examination: a 4-year cross-sectional study - Kubo, Akira (J Phys Ther Sci, 2021)
[Purpose] This study aimed to examine the importance of the level of satisfaction with initiatives toward the national examination of the physical therapy department based on the relationship between the levels of satisfaction with initiatives toward the national examination of the physical therapy and satisfaction with experiences such as activities for job hunting, graduation research, mock test scores of the national examination, and own effort for computer-based testing according to gender in a four-year cross-sectional study. [Participants and Methods] The participants were 202 males and 158 females who graduated from the International University of Health and Welfare, in March from 2017 to 2020. The levels of satisfaction with initiatives toward the national examination of the physical therapy and satisfaction with experiences were assessed using a visual analog scale. The participants were ranked into four 25th percentile groups based on the visual analog scale score of satisfaction with initiatives toward the national examination of the physical therapy. [Results] There was a significant difference in the level of satisfaction with activities for job hunting and mock test scores of the national examination in both males and females, graduation research in males, and own effort for computer-based testing in females. [Conclusion] It is suggested that the degree of satisfaction with initiatives toward the national examination of the physical therapy is related to the level of satisfaction with student life activities and that there are gender differences in this relationship.